ASP.NET MVC 4 recipes : a problem-solution approach - Ciliberti, John (New York, NY : Apress, 2013)
ASP.NET MVC 4 Recipes is a practical guide for developers creating modern web applications, cutting through the complexities of ASP.NET, jQuery, Knockout.js and HTML 5 to provide straightforward solutions to common web development problems using proven methods based on best practices. The problem-solution approach gets you in, out, and back to work quickly while deepening your understanding of the underlying platform and how to develop with it.
Keywords: DESARROLLO DE APLICACIONES WEB; DESARROLLO DE SITIOS WEB